(untitled) (Academia Journal of Medicine, 2020)
Background : Subclinical hypothyroidism could damage vascular function by suggesting enhance in SVR and arterial rigidity and by changing endothelial purpose and so increasing the danger of atherosclerosis and coronary artery disease. The objective of this study is to analyze the relation amid SCH and serum lipid parameters in this subgroup. Subjects and Methods: Current research was performed for the duration of one year at the Department of Medicine, tertiary care institute of India, in patients diagnosed with Sub Clinical Hypothyroidism. Eighty patients were incorporated in the present study and 80 age- and sex-matched and regularly menstruating healthy controls, which were evaluated for the Thyroid Function test, were randomly recruited from staff and volunteers. T3, T4, and TSH were anticipated by utilizing quantitative hard stage ELISA, whereas TC was estimated with photometric determination according to the CHOD PAP method; TG and HDL were estimated by using the enzymatic colorimetric method. Results: There is a momentous augment in the serum TC stage in group II individuals 161.14±48.23 mg/dl when compared to group I 124.35±9.57 mg/dl, it is also a significant amplify in serum LDL-Cholesterol in group II individuals 97.99±32.42 mg/dl when compared to group I individuals 63.35±7.55. Conclusion: Subclinical hypothyroidism (SCH) is linked with increased serum TC and LDL-C levels. As a result, a prospective association amid subclinical hypothyroidism and atherosclerosis occurs. Larger studies are needed to prove this association in Indian patients.